2020
DOI: 10.1080/1389224x.2020.1748669
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming barriers in agri-business development: two education programs for entrepreneurs in the Swedish agricultural sector

Abstract: Purpose: The paper compares two government-sponsored education programs for agricultural entrepreneurs: a Leadership program and a Lean program. Methodology: The paper takes both a qualitative and a quantitative approach in its collection and analysis of data from 54 semistructured interviews and from a survey with 109 participants. Findings: The main challenges to business and personal development are time pressure and the need for better communications. The Leadership program participants emphasize the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…The quasi-experimental studies, mixed-method study design, and pre-post study [63,65,67,70,71,78,80,84,85,[87][88][89] revealed consistent statistical results on the interventions' gains. There were global improvements between pre-and post-intervention.…”
Section: Results Of Interventionsmentioning
confidence: 94%
See 3 more Smart Citations
“…The quasi-experimental studies, mixed-method study design, and pre-post study [63,65,67,70,71,78,80,84,85,[87][88][89] revealed consistent statistical results on the interventions' gains. There were global improvements between pre-and post-intervention.…”
Section: Results Of Interventionsmentioning
confidence: 94%
“…The Leader Practice program (LP) revealed gains in self-leadership and the role of leader; in addition, students achieved gains in understanding the fact that leaders can delegate tasks and responsibilities and recognized the need for continuous improvement in communication with employees and with their family members; in turn, the Lean Agriculture program (LA) proved to be effective in discovering ways of working smoothly, establishing work routines and following previously established procedures, and managing time in a correct way [88].…”
Section: Results Of Interventionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Agri-food is a complex sector, highly driven by business to business (B2B) relationships and commercial associations, making the "valley of death" very wide. The main challenges to translating from ideation to commercialization and business and personal development are lack of entrepreneurial learning time pressures, lack of skilled employees who can come into the business and the need for better communications and less so lack of advice and support and weak alignment between the product/service and the market [105,106]. Farm491 takes an intentionally non-linear approach to supporting entrepreneurs, informed by design thinking principles, where an entrepreneur can plug into each component of the Farm491 incubator offer, allowing for a highly targeted approach to each individual entrepreneur and their needs.…”
Section: Royal Agricultural University (Rau): Case Studymentioning
confidence: 99%